Sequential Regulation of Maternal mRNAs through a Conserved cis-Acting Element in Their 3' UTRs. - Flora, P.; Wong-Deyrup, S.W.; Martin, E.T.; Palumbo, R.J.; Nasrallah, M.; Oligney, A.; Blatt, P.; Patel, D.; Fuchs, G.; Rangan, P. (Cell reports, 2018)
Maternal mRNAs synthesized during oogenesis initiate the development of future generations. Some maternal mRNAs are either somatic or germline determinants and must be translationally repressed until embryogenesis. However, the translational repressors themselves are temporally regulated. We used polar granule component (pgc), a Drosophila maternal mRNA, to ask how maternal transcripts are repressed while the regulatory landscape is shifting. pgc, a germline determinant, is translationally regulated throughout oogenesis. We find that different conserved RNA-binding proteins bind a 10-nt sequence in the 3' UTR of pgc mRNA to continuously repress translation at different stages of oogenesis. Pumilio binds to this sequence in undifferentiated and early-differentiating oocytes to block Pgc translation. After differentiation, Bruno levels increase, allowing Bruno to bind the same sequence and take over translational repression of pgc mRNA. We have identified a class of maternal mRNAs that are regulated similarly, including zelda, the activator of the zygotic genome.